Study on the Relationship Between Market Orientation and Customer-Focused Workplace Culture Amongst Selected Real Estate Organizations in Malaysia - Ong, Yew Leong (2023)
Customer-focused organizations are held together by a central value that every decision begins with customer for advantage. In reality, however, organizations are facing many challenges and internal issues that deter an organization to becoming customer focus. The principal objective of the current study was to examine the relationship between market orientation and customer-focused workplace culture (CFWC). The research model was built by adapting to the theory of market orientation and self-determination. The research uses quantitative method and stratified sampling method to collect data. There were 192 responses in the survey collected from senior employees amongst selected real estate organizations in Malaysia. The researcher first uses PLS-SEM examines the relationships between the behavioral components of market orientation and CFWC. The behavioral components of the current study were customer orientation, information sharing and innovation and creativity. In a separate test, the researcher then uses the disjoint two-stage approach to creates higher order construct model and examines the relationships between market orientation and the research outcome. The researcher outlined two competing explanations of mediation, i.e., internalized extrinsic motivation and intrinsic motivation and then present evidence for each for comparison. In general, this research confirmed that: market orientation, customer orientation and innovation and creativity have positive correlation with CFWC and the relationships are partially mediated through intrinsic motivation; whereas information sharing has no direct effect with CFWC but the relationship is fully mediated through intrinsic motivation. On the contrary, internalized extrinsic motivation has no mediation effect between market orientation and CFWC. This research contributes new insights and produces new model, namely Customer Focus Cultural Means Framework for business leader and professional practitioner who wish to understand about workplace culture, particular on setting and formulating strategy in customer-focused organizations.